ANALITIS SINTETIK TERHADAP STRATEGI PEMBELAJARAN ANDRAGOGI BERPERSPEKTIF KEMANDIRIAN DOSEN DALAM PEMBELAJARAN - Juddah, Abu Bakar (LPPM IAIN Parepare, 2015)
Independence lecturer in planning the establishment, meet implementing, and controlling the evaluation of student learning is something that is absolutely controlled by each lecturer for the demands of the institution should be so. The problem faced is that not all lecturers are present in an institution (such as STAIN Pare Pare) background in education and teacher training, but it does not mean that his lecturers setbeck non teacher can not teach and that setbeck his very independent teacher in teaching. It was, very dependent on the person lecturers each because even if the relevant background in teacher education but do not trigger and push themselves chasing theories and learning strategies inconvensional are grown and emerged as the circulation era of the all probability, the lecturers concerned will tertilap with modern learning and remains proud of its museum convesional theory. Hope the writer of this article in order to share with friends peer (Lecturer) as a form pererekatan silaturrahim and remind them about the application of the results of reading new theories of learning in planning the establishment, meet implementing, and controlling the evaluation of learning, especially in STAIN Pare Pare